T Cell Microvilli: Sensors or Senders? - Kim, Hye-Ran; Jun, Chang-Duk (Frontiers in Immunology, 2019)
Communication between cells is essential for multicellular life. During cognate immune interactions, T cells communicate with antigen-presenting cells (APC) via direct cell–cell contact or the release of molecules and vesicles containing T cell messages. A wide variety of mechanisms have been reported and among them a process called ‘trogocytosis’ has traditionally been thought to be the fastest way to directly transfer membrane portions containing intact proteins from one cell to another; however, the mechanism is unverified. Trogocytosis has been distinguished from the generation of extracellular vesicles (EVs), a term that encompasses exosomes and microvesicles, as EVs are released via a contact-independent manner and are suggested to potentially send molecular messages over a distance. However, some previous reports regarding EVs in T cells may be misleading in terms of explaining their cellular origins. In addition, there is little evidence on how EVs are generated from T cells in vivo and function to regulate complex immune responses. A recent work demonstrated that T cell microvilli—thin and finger-like membrane protrusions—are highly fragile and easily separated as membrane particles by trogocytosis, forming a new class of EVs. Surprisingly, released T cell microvilli-derived particles act as vectors, transmitting T cell messages to cognate APCs. This review focuses on how T cell microvilli vesicles are connected with immune regulation mechanisms discovered previously.